Signal processing for RF circuit impairment mitigation - Huang, Xinping; Zhu, Zhiwen; Leung, Henry (Artech House mobile communications series, 2014)
A wireless communication system employs a radio frequency (RF) wave to transmit information bearing signals. In modern digital communication systems, sophisticated modulation techniques are developed to modulate information onto an RF carrier waveform, so as to transmit more information.